Molecular interaction on imidazolium based ionic liquids and serum albumin: A spectroscopy approach - Kumar Banjare, Manoj; Kumar Banjare, Ramesh; Kumar Ghosh, Kallol (International Journal of Advanced Chemistry, 2020)
Interaction between globular proteins with imidazolium based ionic liquids (ILs) is extremely significant considering that of the vast use of ILs, since protein stabilizer in the current years. The present work, the interaction of human serum albumin (HSA) and bovine serum albumin (BSA) with 1-butyl-3-methylimidazolium octylsulphate (BmimOS) and 1-decyl-3-methylimidazolium tetrafluoroborate (DmimBF4) have been examine the use of fluorescence and FTIR. Fluorescence spectra of HSA/BSA are extinguished by BmimOS /DmimBF4 ILs by way of the dynamic method. The various thermodynamic parameters were revealing that very susceptible interactions exist between HSA/BSA and BmimOS /DmimBF4. The conformational adjustments of HSA/BSA were observed by means of FTIR analysis. Fluorescence methods were completed to find out about the thermal balance of HSA/BSA at different temperature. The thermal balance of BSA in the presence of ILs follows the style BmimOS/DmimBF4 and presence of extra hydrophobic IL, decay increases swiftly as a characteristic of concentration.Â Â